2012
DOI: 10.1103/physrevlett.109.128101
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Indirect Electron Emission from the Green Fluorescent Protein Chromophore

Abstract: Photoelectron spectra of the deprotonated green fluorescent protein chromophore have been measured in the gas phase at several wavelengths within and beyond the S(0)-S(1) photoabsorption band of the molecule. The vertical detachment energy (VDE) was determined to be 2.68 ± 0.1 eV. The data show that the first electronically excited state is bound in the Franck-Condon region, and that electron emission proceeds through an indirect (resonant) electron-emission channel within the corresponding absorption band.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

22
69
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(92 citation statements)
references
References 18 publications
22
69
1
Order By: Relevance
“…4) and contrasts with pHBDI -for which calculations have determined that ADE ≈ VDE. 24,26,[31][32]37 At the optimized D 0 minimum, the main structural changes with respect to S 0 are found in the imidazole ring (see bond lengths in Figure 2), which is consistent with the ring having a formal negative charge in the N(-)-1 anion.…”
supporting
confidence: 56%
See 2 more Smart Citations
“…4) and contrasts with pHBDI -for which calculations have determined that ADE ≈ VDE. 24,26,[31][32]37 At the optimized D 0 minimum, the main structural changes with respect to S 0 are found in the imidazole ring (see bond lengths in Figure 2), which is consistent with the ring having a formal negative charge in the N(-)-1 anion.…”
supporting
confidence: 56%
“…24 Several recent experimental and theoretical investigations of pHBDI -in the gas-phase have identified two dominant competing radiationless relaxation channels -fragmentation, following IC back to the ground electronic state, and electron detachment. 16,18,[24][25][26][27][28][29][30][31][32][33][34] Experimental photoelectron spectroscopy studies and quantum chemistry calculations of gas-phase pHBDI -have revealed that both direct and indirect electron detachment processes play an important role in the deactivation of isolated pHBDI -. 16,18,24,[26][27][28][29][30][31][32][33][34][35] Close to the detachment threshold, around 355 nm, direct photodetachment dominates.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 In GFP, the chromophore is essentially identical to the deprotonated anion of para-hydroxybenzilidene-2,3-dimethylimidazolinone (HBDI -, shown inset in Figure 1f) and has been widely employed as a model to investigate the intrinsic photophysics of the chromophore within the protein. [8][9][10][11][12][13][14][15][16][17][18] In the gas-phase, the S 1 state is wellcharacterised: the S 1 ← S 0 absorption (action) spectrum is similar to that of the protein and its origin is vertically bound relative to the ground state of the neutral (D 0 ). 8,16 The S 1 state decays primarily by internal conversion on a timescale of 1.4 ps; 14 vibrational autodetachment is also an open channel, although this occurs on a 30 ps timescale.…”
Section: Introductionmentioning
confidence: 96%
“…14 A number of recent photoelectron spectroscopy and theoretical studies of gas-phase HBDI have shown that following excitation to the first electronically excited state of a) h.h.fielding@ucl.ac.uk the deprotonated anion, 1 1 ππ*, direct and indirect photodetachment processes compete with internal conversion and fragmentation. [15][16][17] Photoelectron spectra from our group also hinted at the existence of competing electron emission pathways at higher photodetachment energies, however this was not investigated in any detail. 18 Here, we employ a combination of photoelectron spectroscopy and theory to investigate in detail the competition between direct photodetachment and autodetachment of the 2 1 ππ* state of the anion at these higher photodetachment energies, in the range 350-315 nm, within the 2 1 ππ*-S 0 absorption band (Fig.…”
Section: Introductionmentioning
confidence: 98%